P569 Outcomes of IBD patients treated with infliximab: The impact of therapeutic drug monitoring in real-life clinical practice. (16th January 2018) - Kamperidis, N; Middleton, P; Tyrrell, T; Stasinos, I; Arebi, N
Abstract: Background: Infliximab (IFX) is a recognised treatment for inflammatory bowel disease (IBD). 1 Therapeutic Drug Monitoring (TDM) includes measurement of Infliximab trough levels and antibodies to Infliximab (ATI) to optimise treatment and personalise care. 2 We aim to explore the clinical outcomes of TDM for IBD patients on IFX in a real-life setting. Methods: This is a retrospective observational study. Patients on IFX were identified by screening our biologics audit database. TDMs were tested using standard protocol. Primary outcome measure was the rate of IFX discontinuation. Secondary outcomes include the rate of intestinal surgery after IFX initiation and remission rate 6-months after every TDM test. Multivariate binary logistic regression [OR, (95% CI), p value) was performed to identify factors associated with IFX discontinuation and abdominal surgery. Results: Three hundred and forty patients were included with a mean (SD) follow-up of 49.1 (32.7) months. Two hundred and ninety-one had Crohn's disease (CD) and 49 ulcerative colitis (UC) with mean (SD) age of 38.0 (13.5) and 41.6 (15.7) years, respectively. Two hundred and seventy-nine (82.1%) patients (238 CD and 41 UC) were tested for TDM at least once during their follow-up with 759 TDM results. Five hundred and eighty-four (76.9%) TDMs results did not alter patient management. Clinical remission 6 months after TDM testing was associated with 468 (61.7%) TDM tests. One hundred and twelve of 179 patients (40.1%) had undetectable levels and 90 (32.3%) had positive ATI at least once during their follow-up. The mean (SD) Infliximab trough level was 4.1 (3.2) μg/ml. One hundred and sixty-nine patients (49.7%) had their treatment with Infliximab discontinued during the course of follow-up. Treatment was discontinued in 56 (91.8%) patients who were never tested for TDM compared with 113 (40.5%) tested for TDM ( p < 0.01). Fewer TDM tested patients (32; 11.5%) required intestinal surgery post IFX initiation compared with TDM not-tested group (17; 27.9%) ( p < 0.01). TDM was independently associated with IFX discontinuation [OR 19.1, (7.1, 51.2), <0.01] and need for intestinal surgery after IFX initiation [2.2, (1.03, 4.6), 0.04]. Conclusions: Treatment failure with IFX discontinuation and surgery was significantly less frequent with TDM. TDM did not alter management in majority of cases; this may be due to repetitive test to look for transient ATI or to assess effect of treatment adjustment or equivocal indication of annual testing. Further analysis will study outcomes for specific TDM indications. References: 1. Hanauer SB et al. Maintenance infliximab for Crohn's disease: the ACCENT I randomised trial. Lancet, 2002;1541–1549. 2. Niels Vande Casteele et al. Trough concentrations of Infliximab guide dosing for patients with inflammatory bowel disease. Gastroenterology, 2015;1320–1329.